2008
DOI: 10.1179/136485908x337526
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic human carriers ofLeishmania infantum: possible reservoirs for Mediterranean visceral leishmaniasis in southern Iran

Abstract: Over the last decade, the incidence of visceral leishmaniasis (VL) has increased in many districts of the province of Fars, in southern Iran. Recent epidemiological reports indicate that asymptomatic human infections with Leishmania infantum (the causative agent of VL throughout the Mediterranean basin) occur more frequently in Iran than was previously believed. Between 2004 and 2006, blood samples were collected from 802 apparently healthy subjects from communities, in the north-west and south-east of Fars pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 23 publications
3
39
0
1
Order By: Relevance
“…Our DAT results showed that 50 % (3/6), 93.7 % (15/16) of human and dogs were asymptomatic, respectively. Recent epidemiological reports from Iran (Fakhar et al 2008;Alborzi et al 2008) have shown that asymptomatic HVL infection with L. infantum occurs more frequently than was previously believed. Fakhar et al (2008) suggested that those with asymptomatic infection can act as reservoirs for HVL in southern Iran.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our DAT results showed that 50 % (3/6), 93.7 % (15/16) of human and dogs were asymptomatic, respectively. Recent epidemiological reports from Iran (Fakhar et al 2008;Alborzi et al 2008) have shown that asymptomatic HVL infection with L. infantum occurs more frequently than was previously believed. Fakhar et al (2008) suggested that those with asymptomatic infection can act as reservoirs for HVL in southern Iran.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, 1.33 and 32 % of the human and dogs investigated in the present study were found seropositive in a DAT based assay respectively. DAT is a simple, cost-effective and field-applicable method that is often suggested for the field diagnosis of VL in endemic regions and frequently used for that reason in Iran (Mohebali et al 2001(Mohebali et al , 2011Edrissian et al 1999;Fakhar et al 2006Fakhar et al , 2008. The sensitivity and specificity of this method varies in different studies between 90-100 % and 72-100 %, respectively (Sundar and Rai 2002;Fakhar et al 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the most commonly used methods involve iso-enzyme electrophoresis, monoclonal antibodies, specific DNA probes or PCR with or without RAPD analysis (Jaffe and McMahon-Pratt, 1983;Rioux et al, 1990). Several PCR-based assays have been developed to detect and identify leishmanial parasites (Barker, 1989;De Bruijin and Barker, 1992;Piarroux et al, 1994;Osman et al, 1997;Noyes et al, 1998;Fakhar et al, 2008). The results of the present study were encouragingly clear-cut; every test sample produced a single amplicon (that matched, in size, the single amplicon produced from the reference strains of L. major or L. tropica) and the absence of amplicons from the negativecontrol samples indicated the absence of contamination that could have given falsepositive results.…”
Section: Discussionmentioning
confidence: 99%